Production of a Novel Superoxide Dismutase by Escherichia coli and Pichia pastoris and Analysis of the Thermal Stability of the Enzyme - Zhao, Yang; Zhao, Liang; Zhang, Weiwei; Rao, Lei; Wang, Yongtao; Liao, Xiaojun (Frontiers in Nutrition, 2022)
Previously, a new copper-zinc SOD (CuZnSOD) isolated from chestnut rose (Rosa roxburghii) with good stability was described. In this study, the biosynthetic approach was used to create recombinant CuZnSOD. RACE PCR was also used to amplify the full-length CuZnSOD gene from chestnut rose, and the ORF segment was expressed in E. coli BL21 and P. pastoris GS115. For characterization, the enzyme was isolated in two steps in E. coli and one step in P. pastoris. The biochemical properties of the two recombinant enzymes were similar, and their optimal reaction pH and temperature were 6.0 and 50 °C, respectively. According to molecular dynamics simulation, the CuZnSOD showed high stability from 70 °C to 90 °C, and eight amino acids are important for enzyme thermal stability at high temperatures. This study set the stage for industrial manufacture by filling gaps in the link between conformational changes and the thermal stability of the new CuZnSOD.